2019
DOI: 10.1007/s12594-019-1204-y
|View full text |Cite
|
Sign up to set email alerts
|

Uranium Mineralization in Leucogranite of Mastipuram Area, Wanaparti District, Telangana – A New Find

Abstract: The NNW-SSE trending leucogranites in and around Mastipuram, Wanaparthi district, Telangana are intrusive into Peninsular Gneissic complex. The leucogranite is metaluminous to mildly peraluminous, alkali-feldspar granite with I-type signatures, probably formed from a fractionated melt involving crustal component. Magmatic and hydrothermal contributions are supported by wide range of U/Th ratios in mineralized samples, which also show Na-enrichment as compared to non-mineralized leucogranites. Average U and Th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…For example, radon concentrations are higher in granitic areas and lower in other geologic units such as metamorphic rocks or sedimentary rocks, as discussed by Cho et al [10] for 3818 community groundwater system (CGS) wells. Uranium mineralization or uranium minerals including uraninite are commonly found in granitic rocks worldwide [11,13,17,18]. Because the occurrence of secondary uranium minerals is associated with granitic rocks and dykes along with fractures, localization of uranium minerals was emphasized [66,67].…”
Section: Uranium Speciation and Saturation Indices In Groundwatermentioning
confidence: 99%
See 1 more Smart Citation
“…For example, radon concentrations are higher in granitic areas and lower in other geologic units such as metamorphic rocks or sedimentary rocks, as discussed by Cho et al [10] for 3818 community groundwater system (CGS) wells. Uranium mineralization or uranium minerals including uraninite are commonly found in granitic rocks worldwide [11,13,17,18]. Because the occurrence of secondary uranium minerals is associated with granitic rocks and dykes along with fractures, localization of uranium minerals was emphasized [66,67].…”
Section: Uranium Speciation and Saturation Indices In Groundwatermentioning
confidence: 99%
“…Since then, a nationwide survey of groundwater uranium and radon concentrations has been ongoing over 5500 wells in Korea [3][4][5][6][7], with detailed surveys focusing on cities and counties with high proportions of granite distribution [8][9][10]. Many studies have shown that groundwater uranium and radon levels are closely related to bedrock geology, and that their concentrations are highest in granite and granitic gneiss [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%